Delay discounting and anxiety: a systematic review on current evidence for clinical and non-clinical population - Domínguez Rojas, Miguel; Velo Higueras, Carlos (Frontiers in Psychology, 2025)
IntroductionDelay discounting (DD) is a psychological process that involves the tendency to prefer immediate rewards over delayed rewards, even if the latter are greater. The study of this process has been approached from different conceptualisations, including delay discounting, intertemporal choice and temporal discounting. The study of this construct began in the field of economics, but has subsequently been applied to various fields of psychology. There seems to be a generalised tendency among people with various pathologies to prefer immediate and smaller rewards to larger but delayed ones, although this tendency is not clear in the case of people with anxiety.MethodTo study the relationship between anxiety and DD, a systematic review was carried out in accordance with the PRISMA 2020 guidelines, including 25 studies with a total sample of 12,728 subjects from the clinical and general population.ResultsThe results point to a positive relationship between anxiety and DD as found in most studies in both clinical and general populations. Other studies have provided some interesting nuances on this relationship. Only two studies have found a negative relationship between DD and anxiety.Discussion and conclusionThe analysis of our review suggests a positive relationship between DD and anxiety in the general population, although this conclusion is limited by the heterogeneity of results and still cannot be generalised to other populations due to the low representativeness of the clinical population in this review.